Determination of organochlorine and pyrethroid pesticides in fruit and vegetables using solid phase extraction clean-up cartridges. - Sharif, Zawiyah; Che Man, Yaakob; Sheikh Abdul Hamid, Nazimah; Chin, Cheow Keat (Elsevier, 2006)
A method to determine six organochlorine and three pyrethroid pesticides in grape, orange, tomato, carrot and green mustard based on solvent extraction followed by solid phase extraction (SPE) clean-up is described. The pesticides were spiked into the sample prior to analysis, extracted with ethyl acetate, evaporated and reconstituted with a solvent mixture of acetone:n-hexane (3:7). Three different sorbents (Strong Anion Exchanger/Primary Secondary Amine (SAX/PSA), Florisil and C18) were used for the clean-up step. Pesticides were eluted with 5mL of acetone:n-hexane (3:7, v/v) and determined by gas chromatography and electron-capture detection (GC–ECD). SAX/PSA was the sorbent, which provided chromatograms with less interference and the mean recoveries obtained were within 70–120% except for captafol. The captafol recoveries for grape were within acceptable range with C18 clean-up column.